Community Health Development Model to Reduce Sodium Intake in the Food of People, Chachoengsao Province - Hongwachin, Yuphin; Tubtimthong, Wandee (Journal of Preventive Medicine Association of Thailand, 2024)
Objective: The study basic information on sodium consumption, analyze and find components, experiment, and evaluate, and confirm community health development model to reduce sodium consumption. Methods: This research was a mixed methods research. The tools was Interview and a 5-level rating scale questionnaire. Data were analyzed using frequency, percentage, mean, and standard deviation. Verify elements with the consistency model using the LISREL program and a focus group. Results: Most people lacked sodium consumption knowledge. There should be efforts to educate raise awareness about sodium intake, communicate with people in the same direction, teach them how to use technology to search for information, and organize indoor and outdoor housing surroundings suitable to reducing sodium intake. Furthermore, there must be continual surveillance, monitoring, and assessment. 5 main components, 12 sub-components, and 63 indicators. The draft model was used to try it out. It was found that after the training the average was higher than before the training and all experts confirmed community health development model to reduce sodium intake in the food of people, Chachoengsao Province. It was appropriate and could been applied in real life. Conclusion: The community health development model to reduce sodium intake in the food: should start with health care behavior. Lifestyle and dietary changes reduce sodium in the diet. It is an important factor in prevention and reduce the risk of developing chronic non-communicable diseases.